Local responses to national policy: The contrasting experiences of two Midlands cities to the Academies Act 2010. (May 2014) - Smith, Penny; Abbott, Ian
Drawing on data from a series of semi-structured interviews this article reports on findings from a research project focusing on the responses of two local authorities and their secondary schools to the Academies Act 2010. The article considers the background and the development of the education system in both localities. It goes on to focus on issues relating to collaboration, competition, independence and the re-structuring of school governance. For the purposes of the analysis, our theoretical underpinnings drew upon path dependence and Michel Foucault's theories of discourse and power. This framework helped us to illuminate how local conditions had a significant impact on responses to the national policy agenda.